2017
DOI: 10.1088/1538-3873/aa65b0
|View full text |Cite
|
Sign up to set email alerts
|

PandExo: A Community Tool for Transiting Exoplanet Science withJWST&HST

Abstract: As we approach the James Webb Space Telescope (JWST) era, several studies have emerged that aim to: 1) characterize how the instruments will perform and 2) determine what atmospheric spectral features could theoretically be detected using transmission and emission spectroscopy. To some degree, all these studies have relied on modeling of JWST's theoretical instrument noise. With under two years left until launch, it is imperative that the exoplanet community begins to digest and integrate these studies into th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
255
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 323 publications
(256 citation statements)
references
References 25 publications
1
255
0
Order By: Relevance
“…We chose the MIRI band because of the broadness of the 6µm water feature and because, as we are not including any systematic noise floor and observing an M3 star, the noise calculations are similar if the nir-IR simulations are binned to R = 100. These calculations were performed using JWST's publicly available noise simulator, PandExo (Batalha et al 2017) for the same planet system shown in Fig.11. Assuming an observability window comparable to TRAPPIST-1 and an inner edge planet, the planet system would need to be observed through the entirety of Cycle 1 (24 transits) to reach the approximate strength of the water feature.…”
Section: Transit Transmission Spectral Featuresmentioning
confidence: 99%
“…We chose the MIRI band because of the broadness of the 6µm water feature and because, as we are not including any systematic noise floor and observing an M3 star, the noise calculations are similar if the nir-IR simulations are binned to R = 100. These calculations were performed using JWST's publicly available noise simulator, PandExo (Batalha et al 2017) for the same planet system shown in Fig.11. Assuming an observability window comparable to TRAPPIST-1 and an inner edge planet, the planet system would need to be observed through the entirety of Cycle 1 (24 transits) to reach the approximate strength of the water feature.…”
Section: Transit Transmission Spectral Featuresmentioning
confidence: 99%
“…We simulated JWST data using PandExo for three transits observed with the Near Infrared Spectrograph (NIRSpec) G395H grism Bright Object Time Series and Mid-infrared Instrument (MIRI) slitless Low Resolution Spectroscopy with a noise floor of 10 ppm (Batalha et al 2017). We avoided shorter-wavelength instrument modes that may have trouble Figure 10.…”
Section: Future Prospects With Jwst For Gj 436b's Transmission Spectrummentioning
confidence: 99%
“…2.4. JWST Simulator We use PandExo (Batalha et al 2017) 8 to simulate secondary eclipse observations of planets akin to HD 189733b, WASP-80b, and GJ 436b. We chose to simulate spectra using the Near-InfraRed Imager and Slitless Spectrograph's Single Object Slitless Spectroscopy mode (NIRISS SOSS) from 0.6 to 2.8 µm (R=700), Near InfraRed Spectrograph's Grism 395 Medium Resolution mode (NIRSpec G395M) from 2.9 to 5 µm (R=1000), and the Mid-InfraRed Instrument's Low Resolution Spectrometer (MIRI LRS) from 5 to 14 µm (R=100).…”
Section: Spectra Generatormentioning
confidence: 99%